Exploring the Qualities of Ibadurrahman: Insights from Surah Al-Furqan 63-77 in Tafsir Al-Munir by Wahbah Az-Zuhaili - Br Munthe, Rizki Marliana; Sahrin, Abu (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2024)
The concept of Ibadurrahman in the Qur'an, especially in Surah Al-Furqan verses 63-77, offers profound moral and spiritual guidance for Muslims. In this modern era, when social, moral and spiritual challenges are increasingly complex, the characteristics of Ibadurrahman which reflect noble morals and submission to Allah become very relevant. Therefore, this study aims to examine the concept of Ibadurrahman in the Qur'an in Surah Al-Furqan verses 63-77 through the interpretation approach of Al-Munir by Wahbah Az-Zuhaili. This study uses a library research method using a content analysis approach. The results of this research show that Ibadurrahman is not only a group of servants of God with commendable qualities, but is also an example for humanity in living a life of noble character. The characteristics of 'Ibadurrahman according to al-Munir's interpretation include tawadhu, gentleness, diligent in offering night prayers (Tahajud), fear of the punishment of Allah SWT, fair in giving, avoiding polytheism, killing and adultery, avoiding false testimony or speaking lies, receive advice, and pray wholeheartedly to Allah SWT. So as servants we are required to be able to implement the characteristics of 'Ibadurrahman. Konsep Ibadurrahman dalam Al-Qur'an, khususnya dalam Surah Al-Furqan ayat 63-77, menawarkan panduan moral dan spiritual yang mendalam bagi umat Islam. Di era modern ini, ketika tantangan sosial, moral, dan spiritual semakin kompleks, karakteristik Ibadurrahman yang mencerminkan akhlak mulia dan ketundukan kepada Allah menjadi sangat relevan. Oleh karena itu, Penelitian ini bertujuan untuk mengkaji konsep Ibadurrahman dalam Al-Qur’an pada surah Al-Furqan ayat 63-77 melalui pendekatan tafsir Al-Munir karya Wahbah Az-Zuhaili. Penelitian ini menggunakan metode penelitian kepustakaan (Library Research) dengan menggunakan pendekatan content analysis (analisis isi). Hasil penelitian ini menunjukkan bahwa Ibadurrahman bukan hanya sekelompok hamba Allah dengan sifat terpuji, tetapi juga menjadi teladan bagi umat manusia dalam menjalani kehidupan yang berakhlak mulia. Adapun ciri-ciri sifat ‘Ibadurrahman menurut tafsir al-Munir yakni diantaranya tawadhu, lemah lembut, rajin mendirikan shalat malam (Tahajud), takut dengan adzab Allah Swt, adil dalam berinfak, menjauhi syirik, membunuh, dan zina menjauhi persaksian palsu atau berbicara dusta, menerima nasihat-nasihat, serta berdoa dengan penuh hati kepada Allah Swt. Sehingga sebagai seorang hamba kita dituntut agar mampu mengimplementasikan ciri dari sifat ‘Ibadurrahman tersebut.